Evaluating Digital Technology Access and Usage among Teachers - Godfred Sarpong; Michael Osei Tutu Bonsu; Achiaa Adu-Poku (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2023)
This study investigates teachers' access to digital technologies in Public Basic Schools in Asante Akim Central Municipality, Ghana. The study uses a quantitative approach to evaluate the availability and types of Information and Communication Technology (ICT) tools, teachers' motivational and physical comfort with digital technologies, and their skills and usage patterns. Engaging with 108 teachers highlights gaps in access to and use of ICT tools. The results demonstrate that while teachers have access to digital tools such as laptops and smartphones, their access to specific software and digital tools is limited. In terms of motivation, teachers are primarily intrinsically motivated to use digital technologies. Teachers exhibited comfort and confidence in utilizing ICT tools, indicating operational skills and access to ICT. The findings underline the need to address these educational implementation gaps and reduce the digital divide. This research contributes to the literature on digital technology access in developing countries and provides valuable insights for stakeholders involved in integrating educational technology.